First Nations Australians’ self-determination in health and alcohol policy development: a Delphi study - Annalee Stearne; Kylie Lee; S Allsop; A Shakeshaft; M Wright (2022)
Background: Recognition of the role of structural, cultural, political and social determinants of health is increasing. A key principle of each of these is self-determination, and according to the United Nations (2007), this is a right of Indigenous Peoples. For First Nations Australians, opportunities to exercise this right appear to be limited. This paper explores First Nations Australian communities’ responses to reducing alcohol-related harms and improving the health and well-being of their communities, with a focus on understanding perceptions and experiences of their self-determination. It is noted that while including First Nations Australians in policies is not in and of itself self-determination, recognition of this right in the processes of developing health and alcohol policies is a critical element. This study aims to identify expert opinion on what is needed for First Nations Australians’ self-determination in the development of health- and alcohol-related policy. Methods: This study used the Delphi technique to translate an expert panel’s opinions into group consensus. Perspectives were sought from First Nations Australians (n = 9) and non-Indigenous Peoples (n = 11) with experience in developing, evaluating and/or advocating for alcohol interventions led by First Nations Australians. Using a web-based survey, this study employed three survey rounds to identify and then gain consensus regarding the elements required for First Nations Australians’ self-determination in policy development. Results: Twenty panellists (n = 9 First Nations Australian) participated in at least one of the three surveys. Following the qualitative round 1 survey, six main themes, 60 subthemes and six examples of policy were identified for ranking in round 2. In round 2, consensus was reached with 67% of elements (n = 40/60). Elements that did not reach consensus were repeated in round 3, with additional elements (n = 5). Overall, consensus was reached on two thirds of elements (66%, n = 43/65). Conclusions: ...